ANALYSIS OF THE NEED FOR GREEN OPEN SPACE BASED ON OXYGEN REQUIREMENT IN MEDAN CITY - Wahyu Fahreza; Bejo Slamet; Delvian Delvian (Universitas Negeri Medan, 2022)
Medan City is a Metropolitan City with a high population growth rate, in line with the growth rate of regional development. These problems spur the occurrence of land use change. The need for land for residential locations, transportation infrastructure facilities and others will impact the reduced availability of green open space as an oxygen producer in the city of Medan. This study aims to examine the distribution of green open space, estimate the need and adequacy of green open space, and develop directions for developing green open space. This research was conducted from January to completion, using the method of interpretation and analysis of spatial data from quick bird images taken from the SAS Planet application, and calculations were carried out using the Gerarchic formula to determine oxygen demand. The results showed that the area of green open space in Medan City was 86.27 km2 (33%), and non-vegetated/non-green open space was 178.83 km2 or equivalent to (67%) of the Medan City area of 265.10 km2. The oxygen plants produce in green open spaces is 4,367,418.75 kg/day. Meanwhile, the oxygen demand in Medan City is 5,150,425.98 kg/day, and when converted into green open space, it is 101.74 km2. Directions for the development of green open spaces can be carried out in several ways, namely managing green spaces, synergizing the natural and artificial environment, implementing a low-cost transportation system, empowering population policy strategies, utilizing water and energy resources, maintaining environmental health based on city planning that favours development principles sustainable.Keywords: Green open space, Oxygen, Quickbird Image, Medan